2001
DOI: 10.1523/jneurosci.21-18-07340.2001
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Long-Term Memory Is Related to Mossy Fiber Synaptogenesis

Abstract: Structural synaptic changes have been suggested to underlie long-term memory formation. In this work, we investigate if hippocampal mossy fiber synaptogenesis induced by water maze overtraining can be related with long-term spatial memory performance. Rats were trained in a Morris water maze for one to five identical daily sessions and tested for memory retrieval 1 week and 1 month after training. After the last test session, the rat brains were obtained and processed for Timm's staining to analyze mossy fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
123
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(133 citation statements)
references
References 53 publications
7
123
2
1
Order By: Relevance
“…Importantly, this occurs during the 7-d post-training period at a time when the animal is no longer exposed to the training apparatus, experimental room, or experimenters. Thus, the growth process occurs off-line and, as has been previously shown, persists for at least 30 d (Ramirez-Amaya et al 2001).…”
supporting
confidence: 62%
See 2 more Smart Citations
“…Importantly, this occurs during the 7-d post-training period at a time when the animal is no longer exposed to the training apparatus, experimental room, or experimenters. Thus, the growth process occurs off-line and, as has been previously shown, persists for at least 30 d (Ramirez-Amaya et al 2001).…”
supporting
confidence: 62%
“…Moreover, the significant training-dependent increments in the SOSP of HIDDEN rats were restricted to the rostralmost third of the septal hippocampus ( Fig. 2A), a point emphasized by both Ramirez-Amaya et al (2001) and Holahan et al (2006).In rats sacrificed 48 h after training, the size and relative distribution of MFTFs did not differ as a function of training. Specifically, no significant effect of training on the size of the SOSP, the SL, or the SOSP/SL within the regio inferior was found (data not shown).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Numerous early and recent studies demonstrated that a flat retrograde amnesia was induced by lesions of dHC and the entire HC at 0.5-3.5 months in watermaze memory retention (Bolhuis et al, 1994;Mumby et al, 1999; logical changes found in CA3 stratum oriens (Ramirez-Amaya et al, 2001) and may indicate involvement of the CA3 autoassociative network in recent (Nakazawa et al, 2002(Nakazawa et al, , 2003Meilandt et al, 2004) as well as in long-term memory storage and recall. Mapping data support the idea that DG is not only involved in memory encoding but also participates in memory retrieval (Nanry et al, 1989;Lisman, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The learning deficit exhibited by heterozygous Marcks mutant mice appears to be specific to spatial navigation and does not extend to contextual aspects of hippocampal function and is most apparent following prior training to a different spatial location (spatial reversal learning) . Previous studies suggest that mossy fiber synaptic plasticity may be important for hippocampus-dependent spatial learning processes (Ishihara et al, 1997;Lassalle et al, 2000;Ramirez-Amaya et al, 2001), and naturally occurring variations in hippocampal infrapyramidal mossy fiber distribution in inbred mice are specifically correlated with spatial reversal learning performance (Schopke et al, 1991;Bernasconi-Guastalla et al, 1994). In agreement with the pattern of synaptic and behavioral deficits observed in heterozygous Marcks mutant mice, mice lacking the synaptic vesicle binding protein Rab3a also exhibit deficits in mossy fiber LTP, but not PPF or basal synaptic transmission (Castillo et al, 1997), and deficits in spatial reversal learning, but not initial spatial acquisition or contextual fear conditioning (Hensbroek et al, 2003;D'Adamo et al, 2004).…”
Section: Discussionmentioning
confidence: 99%